2015
DOI: 10.1007/s10544-014-9924-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro release of cupric ion from intrauterine devices: influence of frame, shape, copper surface area and indomethacin

Abstract: The release of cupric ion from copper intrauterine device (Cu-IUD) in human uterus is essential for contraception. However, excessive cupric ion will cause cytotoxic effect. In this paper, we investigated the influence of device characteristics (frame, copper surface area, shape, copper type and indomethacin) on copper release for the efficacy and adverse effects vary with IUD types which may correlate to their different release behaviors. Nine types of Cu-IUDs were selected and incubated in simulated uterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In the early years, most IUDs were steel rings (designated as O-shaped in this study) due to its low cost, and the devices were provided free of charge in some hospitals [ 1 , 22 ]. Later, the copper-releasing IUDs replaced the steel rings as many problems were encountered by using the rings [ 29 ].Nowadays, copper-releasing IUDs have become the prevailing devices in clinical application in China [ 22 , 24 ]. Recently, the levonorgestrel intrauterine system (LNG-IUS) along with other optimized IUDs were also provided to Chinese women [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early years, most IUDs were steel rings (designated as O-shaped in this study) due to its low cost, and the devices were provided free of charge in some hospitals [ 1 , 22 ]. Later, the copper-releasing IUDs replaced the steel rings as many problems were encountered by using the rings [ 29 ].Nowadays, copper-releasing IUDs have become the prevailing devices in clinical application in China [ 22 , 24 ]. Recently, the levonorgestrel intrauterine system (LNG-IUS) along with other optimized IUDs were also provided to Chinese women [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, the use switched to T-shaped copper IUDs, although a large population of women was still using the steel rings [ 21 ]. Today, there are dozens of different types of IUDs available on the market that clearly mirror their clinical application [ 22 24 ]. Most of the IUDs used in China are manufactured in China, and the majority is the copper-releasing IUDs, including all types of T-shaped and V-shaped copper-releasing IUDs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of additional authors reported the use of SUFs in studying copper, zinc, or indometacin release from IUDs (40)(41)(42)(43)(44)(45)(46)(47). However, in all of these studies, the media designed by Zhang et al (35) or the slightly modified version reported by Mora et al (39) were applied.…”
Section: Media Simulating Human Uterine Fluidmentioning
confidence: 99%
“…The Chinese have produced five different copper IUDs containing indomethacin with the goal of reducing menstrualrelated complaints that occur with currently available copper IUDs. [45][46][47] The indomethacin does not interfere with copper ion release and the copper does not interfere with indomethacin action. 47 One such device, the Medicated Gamma IUD, is a gammashaped stainless steel wire frame, with 250 mm 2 of spiraled copper wire on a 26 mm  26 mm frame.…”
Section: Copper Indomethacin Intrauterine Device (Available In China)mentioning
confidence: 99%
“…Silicon rubber containing indomethacin 18 mg lines the inside of the stainless steel wire tube that makes up the IUD frame. 46 Unfortunately limited data are available in the English literature to understand all of the various frames, efficacy, and side effects of these medicated IUDs; however, one review article includes a nonreferenced table of a few Chinese copper IUDs, with pregnancy rates ranging from 0.46 to 2.73%, and effective duration between 5 and 10 years. 46…”
Section: Copper Indomethacin Intrauterine Device (Available In China)mentioning
confidence: 99%